Viral Evasion of Innate Immune Defense: The Case of Resistance of Pandemic H1N1 Influenza A Virus to Human Mannose-Binding Proteins - White, Mitchell R.; Nikolaidis, Nikolaos M.; McCormack, Francis; Crouch, Erika C.; Hartshorn, Kevan L. (Frontiers in Microbiology, 2021)
Mannose binding lectins effectively inhibit most seasonal strains of influenza A virus and contribute to innate host defense vs these viruses. In contrast, pandemic IAV strains are largely resistant to these lectins, likely contributing to increased spread and worse outcomes. In this paper we evaluated inhibition of IAV by mannose binding lectins of human, bacterial and fungal origin to understand and possibly increase activity vs pandemic IAV. A modified version of human surfactant protein D (SP-D) neck and carbohydrate recognition domain (NCRD) with combinatorial substitutions at the 325 and 343 positions, previously shown to inhibit pandemic H3N2 IAV in vitro and in vivo, and to inhibit pandemic H1N1 in vitro, failed to protect mice from pandemic H1N1 in vivo in the current study. We attempted a variety of maneuvers to improve activity of the mutant NCRDs vs 2009 pandemic H1N1, including formation of full-length SP-D molecules containing the mutant NCRD, cross-linking of NCRDs through use of antibodies, combining SP-D or NCRDs with alpha-2-macroglobulin, and introducing an additional mutation to the double mutant NCRD. None of these substantially increased the antiviral activity for pandemic H1N1. We also tested the activity of bacterial and algal mannose binding lectins, cyanovirin and griffithsin, against IAV. These had strong activity against seasonal IAV which was largely retained against pandemic H1N1. We propose mechanisms to account for differences in activity of SP-D constructs against pandemic H3N2 and H1N1 and for differences in activity of cyanovirin vs SP-D constructs.